2005
DOI: 10.1007/s00024-004-2648-5
|View full text |Cite
|
Sign up to set email alerts
|

Site Effect and its Relationship to the Intensity and Damage Observed in the June 27, 1998 Adana-Ceyhan Earthquake

Abstract: The site response at 15 stations in the Adana-Ceyhan region (Southern Turkey) is calculated from the recordings of aftershocks of June 27, 1998 Adana-Ceyhan earthquake (M S ¼ 6.2) by using the Standard Spectral Ratio (SSR) and the Horizontal-to-Vertical Spectral Ratio (HVSR) methods. While the two methods are in good harmony at a few stations in determining the site effects, they show differences on the estimated amplifications or on the site resonance frequencies at most stations. It was not clear which one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…For the local response, the mean soil and rock amplification functions is used. Yalcinkaya and Alptekin (2005a) estimated site-specific amplification functions from the weakmotion recordings at 15 stations located in the AdanaCeyhan region. It is considered that the geologic characteristics underlying their stations display similarities with those of our stations, because all stations are located in the same tectonic area, albeit even if their locations are different.…”
Section: Methods and Modeling Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…For the local response, the mean soil and rock amplification functions is used. Yalcinkaya and Alptekin (2005a) estimated site-specific amplification functions from the weakmotion recordings at 15 stations located in the AdanaCeyhan region. It is considered that the geologic characteristics underlying their stations display similarities with those of our stations, because all stations are located in the same tectonic area, albeit even if their locations are different.…”
Section: Methods and Modeling Parametersmentioning
confidence: 99%
“…Even if the discussions about the accuracy of results of the Horizontalto-Vertical Spectral Ratio method continue; that is, it usually underestimates true amplifications (e.g. Yalcinkaya and Alptekin, 2005a), we were forced to use the results of this method for the mean rock amplification function, because it was impossible to define the best rock station for reference. The mean soil and rock amplification functions and their standard deviations derived for this study are presented in Fig.…”
Section: Methods and Modeling Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent destructive earthquakes have shown evidences of the effects of surface and subsurface geology and topography on ground motion characteristics at a given site. Among these effects we have: amplification and attenuation patterns, strong spatial variability of amplification and polarization with in a small area [1, 2,3]. Several earthquakes such as the 1985 Michoacan (Mexico), 1988 Spitak (Armenia), 1990, and 2003 Bam (Iran) earthquakes have clearly demonstrated that local soil and sediment conditions (site effect or site specific condition) can have a significant influence on the ground motion and damage pattern, respectively [1, 2,4].…”
Section: Isbn 978-93-84468-11-8 Proceedings Of International Conferenmentioning
confidence: 99%
“…Among these effects we have: amplification and attenuation patterns, strong spatial variability of amplification and polarization with in a small area [1, 2,3]. Several earthquakes such as the 1985 Michoacan (Mexico), 1988 Spitak (Armenia), 1990, and 2003 Bam (Iran) earthquakes have clearly demonstrated that local soil and sediment conditions (site effect or site specific condition) can have a significant influence on the ground motion and damage pattern, respectively [1, 2,4]. In the other word, Ground shaking and its associated damage to engineered structures can be strongly influenced, not only by source and path effects, but also by surface and sub-surface geological (depth and type of bedrock, underground sediments) and geomorphologic conditions in the vicinity, known as "local site effects".…”
Section: Isbn 978-93-84468-11-8 Proceedings Of International Conferenmentioning
confidence: 99%